A federated approach to parallel and distributed simulation of complex systems - Sikora, Andrzej; Niewiadomska-Szynkiewicz, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
The paper describes a Java-based framework called ASimJava that can be used to develop parallel and distributed simulators of complex real-life systems. Some important issues associated with the implementation of parallel and distributed simulations are discussed. Two principal paradigms for constructing simulations today are considered.
Keywords: parallel simulation; distributed simulation; federated simulators; computer networks simulation; Frame Relay